2011
DOI: 10.5539/elt.v4n3p214
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Iranian EFL High School Students’ Multiple Intelligence Scores and their Use of Learning Strategies

Abstract: According to the theory of multiple intelligences (MI) propounded by Gardner (1983Gardner ( , 1999aGardner ( , 1999b, each individual has a multitude of intelligences that are quite independent of each other and each individual has a unique cognitive profile. Having access to the MI profiles and learning strategies of learners could help the teachers in planning activities to connect both strategies and students' talents and provide students with the best possible instruction. Thus, this study attempts to find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
0
10
0
3
Order By: Relevance
“…Utilizing this theory in classroom management and class classification, can help teacher to give the needs of students with particular intelligence. 44 According to the student's achievement data we can conclude that student educated with Multiple Intelligences theory gain high score even almost perfect. It can be said that the implementation of MI theory in the learning process have been effective.…”
Section: Arabiyâtmentioning
confidence: 96%
“…Utilizing this theory in classroom management and class classification, can help teacher to give the needs of students with particular intelligence. 44 According to the student's achievement data we can conclude that student educated with Multiple Intelligences theory gain high score even almost perfect. It can be said that the implementation of MI theory in the learning process have been effective.…”
Section: Arabiyâtmentioning
confidence: 96%
“…Akbari and Hosseini (2008) investigated the relationship between EFL learner's MI and strategy use. Also Hajhashemi, et al (2011) investigated the relationship between LLS and MI. These results also support what Baş and Beyhan (2010) claimed about the important role of MI in language learning process.…”
Section: Responding To the Research Question Onementioning
confidence: 99%
“…Various studies revealed the benefits of multiple intelligences in learners' achievement (Razmjoo, 2008;Gupton, 2011), learning strategies (Hajhashemi, Ghombavani, & Amirkhiz, 2011). Therefore this study was aiming to measure multiple intelligences profiles of junior secondary school students that is important due to improve the classroom activities.…”
Section: Introductionmentioning
confidence: 99%